Adherence to iron chelation therapy and associated healthcare resource utilization and costs in Medicaid patients with sickle cell disease and thalassemia. (3rd March 2016) - Vekeman, Francis; Sasane, Medha; Cheng, Wendy Y; Ramanakumar, Agnihotram V.; Fortier, Jonathan; Qiu, Ying; Duh, Mei Sheng; Paley, Carole; Adams-Graves, Patricia
Abstract: Background: Sub-optimal patient adherence to iron chelation therapy (ICT) may impact patient outcomes and increase cost of care. This study evaluated the economic burden of ICT non-adherence in patients with sickle cell disease (SCD) or thalassemia. Methods: Patients with SCD or thalassemia were identified from six state Medicaid programs (1997–2013). Adherence was estimated using the medication possession ratio (MPR) of ≥0.80. All-cause and disease-specific resource utilization per-patient-per-month (PPPM) was assessed and compared between adherent and non-adherent patients using adjusted incidence rate ratios (aIRR). All-cause and disease-specific healthcare costs were computed using mean cost PPPM. Regression models adjusting for baseline characteristics were used to compare adherent and non-adherent patients. Results: A total of 728 eligible patients treated with ICT in the SCD cohort, 461 (63%) adherent, and 218 in the thalassemia cohort, 137 (63%) adherent, were included in this study. In SCD patients, the adjusted rate of all-cause outpatient visits PPPM was higher in adherent patients vs non-adherent patients (aIRR [95% CI]: 1.05 [1.01–1.08], p < 0.0001). Conversely, adherent patients incurred fewer all-cause inpatients visits (0.87 [0.81–0.94], p < 0.001) and ER visits (0.86 [0.78–0.93], p < 0.001). Similar trends were observed in SCD-related resource utilization rates and in thalassemia patients. Total all-cause costs were similar between adherent and non-adherent patients, but inpatient costs (adjusted cost difference = −1530 PPPM, p = 0.0360) were lower in adherent patients. Conclusion: Patients adherent to ICT had less acute care need and lower inpatient costs than non-adherent patients, although they had more outpatient visits. Improved adherence may be linked to better disease monitoring and has the potential to avoid important downstream costs associated with acute care visits and reduce the financial burden on health programs and managed care plans treating SCD and thalassemia patients.